Unity and Diversity of Neplese Culture - Gautam, Murari Krishna (Patan Prospective Journal, 2023)
The Nepalese population is not the product of an intimate miscegenation of a number of diverse races and there can found more racial ramifications, with separate languages and customs connected with them. They may have come from outside or some of them may be traced as aborigine groups, and there may be the evidences of racial, geographical and economic diversities, but so far the "cultural milieux" is concerned it's the out product and supra-product of the common racial contribution of different languages and cultural groups of Nepalese people. We are at present conscious of a common Nepalese Ness of outlook although are some 'agent provocative' of Indian sub-cont endeavoring much to 'discrep and divast' the Nepalese cultural unity discarding Hinduism on the basis of sectarianism, regionalism and so called aboriginalisms. It is, being the source of violence, which can disintegrate the nation ultimately. For the communalists Hinduism is but a 'stratagem or intrigue' created by 'Bahun and Chhetries' for the exploitation, suppression, oppression and recognized as 'Ko domination of and against other castes and ethics groups. They promote the ideas of' Magarata' 'Khasana' 'Sesants' 'Lembuana' 'Kerata' 'Gyu-Rong' (regions of nine chiefs of Gurungs) 'Tharuwana' etc. as new Hindu people with their separate petty states, which may by the later half of the 18th century. Prithivi Narayan Shah, The Hindu King had Conquest and proclaimed" Yo Asala Hindustana ho". His political unification was followed by Codification to legitimatize, the Hindu autocratic authority through Hindu social law. According to them did not change the ideology received as a legacy from the past regime and constitutionally declared Nepal Thanas. The Deur as a Hindu state and kingdom.